Prevalence of Trypanosoma Among Cattle Found in Grazing Hotspots in Jalingo Metropolis, Taraba State, Nigeria - Sarah Baba Gurama; Wama Binga Emmanuel; Stephen Dio Titus; Vera Akwa Yafeh; David Christopher Bando; Munirah Ibrahim Foku; Usman Kesunga Yakubu (Journal of Multidisciplinary Science: MIKAILALSYS, 2025)
Bovine trypanosomiasis, commonly referred to as nagana, poses a significant threat to cattle populations across various regions in Africa, particularly in Nigeria. This disease caused by protozoan parasites of the genus Trypanosoma and transmitted by infected tsetse flies, results in extensive economic losses due to decreased productivity, fertility issues, and increased mortality rates among livestock. This study focuses on the prevalence of bovine trypanosomiasis in Jalingo, Taraba State, Nigeria a critical hub for cattle trade amidst the challenges posed by varied ecological factors and management practices that influence disease dynamics. Our research assessed 113 cattle samples collected from different grazing hotspots using both microscopy and polymerase chain reaction (PCR) techniques. The overall prevalence was found to be 17.7%, with notable concentrations of positive cases in specific locations. Factors such as age, breed, and the educational background of herders were significantly associated with infection rates. Notably, all positive cases were reported among herders lacking formal education, indicating a potential link between educational attainment and effective disease management. Furthermore, the White Fulani breed exhibited a higher susceptibility to the disease compared to other breeds evaluated. The results emphasize the necessity for targeted intervention strategies, including enhancing diagnostic capabilities, public awareness campaigns, and educational initiatives aimed at cattle herders. Strengthening healthcare infrastructure and ongoing research into disease transmission dynamics are essential for controlling bovine trypanosomiasis and mitigating its impact on the livestock industry in Nigeria.